Planning for Gender Parity: Built Environment Barriers to Bikeshare Demand - Auch, Casey. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2023.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Sumeeta Srinivasan.; Committee: Mark Chase.; Keyword: Urban planning.